Nursing Students' Perception of Wearing Mask and Taking Coronavirus Vaccines - Sameerah Mohammed Saeed, Mohammed Baqer Al-Jubouri, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The World Health Organization was declared COVID-19 a pandemic on March 11, 2020. As a result, to keep the coronavirus under control, protective technique like face covering is required. Vaccination, on the other hand, is regarded as a preventative and effective measure. As nursing students play an important role in the future of nursing, their perception regarding wearing mask and taking vaccine can be crucial in preventive measures regarding COVID-19. Objective: The purpose of this study was to assess the perception of nursing students’ regarding wearing mask and coronavirus vaccines. Design: A descriptive correlational design was used to guide this study. Settings and Participants: A total of 255 undergraduate nursing students in six colleges of nursing at six different universities in Iraq were selected by convenience sampling. All participants were invited to complete the questionnaire through Google Form from February 14, 2022 to February 24, 2022. Methods: The sampling method was applied in this study using a non-probability purposive method. Data were collected using an online questionnaire consisted of demographic characteristics and 32 items about the Face Mask Perception Scale and 11 items about VAC-COVID-19 scale. Results: The results indicated that the majority of students had a positive perception of wearing facial masks (n = 210; 82.4%). The study results also displayed that less than a half had an unsound perception of coronavirus vaccine (n = 123; 48.2%), followed by those who had somewhat sound perception (n = 120; 47.1%), and those who had sound perception (n = 12; 4.7%). Conclusions: As future nurses, nursing students can play a critical role in educating patients about COVID-19 risks and benefits. Findings suggested that nursing students need to consider vaccine concerns and provide vaccine development education.